RESILIENCE BUILDING AGAINST CYBER INSECURITIES IN THE BALTICS (Security Dialogues, 2024)
The Global Risk Report of the World Economic Forum has been defining cyberinsecurity as one of the severe global risks since 2023. The Global Risk Report 2024 rankedcyber insecurity as the eight global risk by severity over a ten-years-period. The peacefulenvironment the cyberspace had provided for almost two decades ended with the release ofthe Morris Worm, the first harmful malware, in 1988. Since then cyber threats and cyberattacks have been posing serious dangers to national security. The cyber-attacks on Estoniain 2007 owing to the Bronze Soldier event are considered as an important milestone incybersecurity studies. These were followed by the cyber-attacks on Georgia in 2008 and onIran in 2010, which created a serious need for cyber policies, actions, strategies and normsat national and international level like the efforts of the UN, NATO and OECD to overcomethe unwanted results of the cyber domain. This study will deal with the Baltic states’ cybercapabilities, cyber capacity building, security concerns and cybersecurity challenges from theperspective of small states’ security considering the latest developments in Eastern Europesince 2022, the fast advancements in information technology and artificial intelligence. Thestudy will be a desk research focusing on the national strategies, policies and action plansof the Baltic states to fight with the insecurities of cyberspace by using case study analysisas a research method. This study aims to shed light on the vulnerabilities and resilience ofthe Baltic states facing with cyber insecurities. The scholarship will contribute into Baltic andcyber security studies.